Cognition and quality of life relationship among the elderly community: a cross-sectional study - Barbara Maria Lopes da Silva Brandão; Alice Maria Barbosa da Silva; Rafaella Queiroga Souto; Fabia Alexandra Pottes Alves; Gleicy Karine Nascimento de Araújo; Viviane Cristina Fonseca da Silva Jardim; Hulda Vale de Araújo (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to assess cognitive functions and their association with quality of life among elderly people enrolled in a Family Health Unit (FHU) of Primary Health Care in Recife-PE. Methods: a quantitative, descriptive, cross-sectional study in which elderly aged 60 years and over were studied. Results: 76.7% of the elderly were women and the age group was less than or equal to 70 years. 68.6% had cognitive impairment, and in the quality of life assessment it was found that the social participation facet had the highest mean score among the elderly (14.25), while the lowest was observed in the sensory functioning facet (9.10). There was an association between cognitive decline and quality of life. Conclusion: most of the elderly had good quality of life rates, but low cognitive level. Using screening tools allows early detection of health problems, guiding the nursing staff in the construction of preventive measures.